A practical strategy for chemical profiling of herbal medicines using ultra-high performance liquid chromatography coupled with hybrid triple quadrupole-linear ion trap mass spectrometry: a case study of Mori Cortex. Issue 2 (25th November 2014) - Jing, Wanghui; Yan, Ru; Wang, Yitao
Abstract : A MIM-IDA-EPI-based strategy was proposed as a practical tool for the comprehensive characterization of the chemical profile of Mori Cortex. Abstract : Herbal medicines (HMs) are believed to produce holistic action through the synergistic effects of many major and minor components. In the current study, a practical strategy was designed to comprehensively characterize the chemical constituents in HMs. Mori Cortex (MC), which contains diverse chemical constituents and consequently exhibits a broad spectrum of pharmacological activities, was chosen as a model case. The workflow included three steps: first, a thorough literature review was performed to summarize the available information about the phytochemistry and the biosynthetic pathways for the genus Morus ; second, seven compounds, namely morin (polyhydroxyflavonoid), morusin (prenylflavone), mulberroside A and oxyresveratrol (stilbenes), mulberroside C (2-arylbenzofuran derivative), sanggenon C and kuwanon G (DA-type adducts), were selected to propose mass fragmentation pathways for the primary chemical types in MC; and third, a set of parent-to-parent ion transitions was constructed using quasi-molecular and sodium adduct ions of the identified compounds and their potential derivatives, and the multiple ion monitoring-information dependent acquiring-enhanced product ion (MIM-IDA-EPI) method was thereby used to detect and identify the constituents. As a result, a total of 140 components were detected with 133 identified in the MC extract, including 10 polyhydroxyflavonoids, 4 stilbenes, 16 2-arylbenzofuran derivatives, 60 prenylflavones, and 43 DA type adducts, while the identities of 7 components could not be elucidated due to insufficient structural information. Collectively, the strategy was demonstrated to be efficient, reliable and sensitive for global chemical profiling of HMs.